THE IMPACT OF TRUST ON LEADERSHIP DURING MERGERS AND ACQUISITIONS: CASE STUDIES FROM THE INDIAN TELECOM SECTOR - Mishra, Arjyalopa; Pradhan, Amruta; Bisht, Oasis (PEOPLE: International Journal of Social Sciences, 2018)
Managing employees’ trust on the organization, during mergers and acquisitions is definitely a critical leadership challenge in today’s global environment. Prior leadership research has been an evidence of how a leader communicates during a downsizing event with the employees who would be expected to feel more vulnerable can create the foundation for future trust in the leader. (Kasper-Feuhre and Ashkanasy, 2001). This paper explores the dynamics of trust during post-merger and acquisition integration planning in the Indian Telecom Sector. This study is purely doctrinal in nature, focusing on secondary sources which helps in examining major mergers in the telecom Industry in India namely Vodafone-Hutchison Essar Merger in 2007, Idea and Spice Telecom merger in 2008, Reliance Industries and Infotel merger in 2010, Vodafone and Idea Merger, Bharti Airtel and Telenor Merger, Tata Teleservices and Bharti Airtel merger. The objective behind the study of these mergers is to understand the cultural disparity in the organizations and the leadership role in the cultural amalgamation of the participating companies for retaining the employees. Further this paper attempts to understand the role of trust in the organization as well as on the leader, post the merger when the employees are already experiencing a level of estrangement. The significance of analysing these perspectives in the above mentioned specific cases is to bring out the factors responsible for successful mergers and the consequences of failed mergers from a human resource perspective.